2004
DOI: 10.1017/s002211200400919x
|View full text |Cite
|
Sign up to set email alerts
|

Oblique particlewall collisions in a liquid

Abstract: This paper presents experimental measurements of the approach and rebound of a particle colliding obliquely with a wall in a viscous fluid. Steel and glass particles 12.7 mm in diameter were used. The experiments were performed using a thick Zerodur wall (a glass-like material) with various mixtures of glycerol and water. Normal and tangential coefficients of restitution were defined from the ratios of the respective velocity components at the point of contact just prior to and after impact. These coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
151
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 39 publications
20
151
0
Order By: Relevance
“…3͒ trend downwards with successive collisions, from e = 0.97± 0.04 at the first collision to e = 0.84± 0.03 at the eighth impact. This agrees with previous experiments, [3][4][5] which found that the restitution coefficient diminishes with decreasing Stokes number St= 2 9 S DH ͉ ˙2 − ˙1 ͉ cos 1 / L . The enhanced upswing observed despite these collisional losses indicates that they are overshadowed by other effects, which we characterize using the following model.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…3͒ trend downwards with successive collisions, from e = 0.97± 0.04 at the first collision to e = 0.84± 0.03 at the eighth impact. This agrees with previous experiments, [3][4][5] which found that the restitution coefficient diminishes with decreasing Stokes number St= 2 9 S DH ͉ ˙2 − ˙1 ͉ cos 1 / L . The enhanced upswing observed despite these collisional losses indicates that they are overshadowed by other effects, which we characterize using the following model.…”
supporting
confidence: 93%
“…3,5 To clarify the interplay between vortex motions and immersed collisions, we conducted experiments with both isolated and colliding spheres, in the pendulum configurations illustrated in Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where w p is the particle velocity of grain size D. It has been found that particle impacts are completely damped for St <~30 [Schmeeckle et al, 2001;Joseph and Hunt, 2004]. When the Stokes number is calculated for sand in the Wax Lake Outlet (D = 176 μm), and w p is set to the effective particle impact velocity (w i,eff , Table 4), St = 11.…”
Section: The Tools Effectmentioning
confidence: 99%
“…The dependence of the coefficient of restitution on the Stokes number was also presented in the work by Gondret, Lance & Petit (2002); in this study, the authors measured the normal trajectory of the particle over multiple bounces. Joseph & Hunt (2004) examined oblique collisions between a particle and a wall. Later work by Yang & Hunt (2006) measured the coefficient of restitution for particle-particle collisions in a liquid and found a similar dependence on particle Stokes number.…”
Section: Introductionmentioning
confidence: 99%